2013
DOI: 10.1371/journal.pone.0066820
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Neuronal Oscillatory Correlates of Working Memory Performance

Abstract: PurposeWorking memory (WM) represents the brain’s ability to maintain information in a readily available state for short periods of time. This study examines the resting-state cortical activity patterns that are most associated with performance on a difficult working-memory task.MethodsMagnetoencephalographic (MEG) band-passed (delta/theta (1–7 Hz), alpha (8–13 Hz), beta (14–30 Hz)) and sensor based regional power was collected in a population of adult men (18–28 yrs, n = 24) in both an eyes-closed and eyes-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
2
9
1
Order By: Relevance
“…The above discussed results were confirmed by using individual (i.e., IAF-based) band definitions rather than fixed pre-defined frequency bands [ 55 ]. Similar results were described in our previous study, which compared the spectral power between children and adults using EEG [ 18 ], as well as in previous studies utilizing MEG [ 58 , 59 ]. Several EEG-fMRI studies have also shown absolute mean power differences between both EC and EO conditions during the resting state[ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 88%
“…The above discussed results were confirmed by using individual (i.e., IAF-based) band definitions rather than fixed pre-defined frequency bands [ 55 ]. Similar results were described in our previous study, which compared the spectral power between children and adults using EEG [ 18 ], as well as in previous studies utilizing MEG [ 58 , 59 ]. Several EEG-fMRI studies have also shown absolute mean power differences between both EC and EO conditions during the resting state[ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 88%
“…This finding is similar to observations in young adults under basal conditions. In fact, it has been shown that better performance in a three-back verbal working memory task is related to higher theta activity recorded under basal conditions (Heister et al 2013). Thus, the increase of these low levels of theta activity under incidental memory and intentional learning observed in mature adults under basal and incidental learning could be an EEG correlate of neural processes that account for the mature adults' performance under incidental memory and intentional learning conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Traditionally, the EO-induced alpha suppression, also termed “alpha block” (Niedermeyer, 1999), has been interpreted as a replacement by higher frequencies which is indeed suggested by visual inspection of the raw EEG signal. However, numerical comparisons indicate a decrease in wideband power upon opening the eyes, albeit the decrease in the beta band is usually smaller than in the alpha band (Barry et al, 2007; Heister et al, 2013; Ishii et al, 2013). Overall, effects of the pharmacological manipulation with moderate alcohol intoxication were weaker than the EOC effects, with alcohol increasing power in alpha and beta bands, especially under the eyes-closed condition.…”
Section: Discussionmentioning
confidence: 98%